2021
DOI: 10.1111/odi.13845
|View full text |Cite
|
Sign up to set email alerts
|

Development of a rat model for type 2 diabetes mellitus peri‐implantitis: A preliminary study

Abstract: Objective To develop an in vivo model to simulate the complex internal environment of diabetic peri‐implantitis (T2DM‐PI) model for a better understanding of peri‐implantitis in type 2 diabetic patients. Materials and methods Maxillary first molars were extracted in Sprague‐Dawley (SD) rats, and customized cone‐shaped titanium implants were installed in the extraction sites. Thereafter, implants were uncovered and customized abutments were screwed into implants. A high‐fat diet and a low‐dose injection of stre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 62 publications
3
13
0
Order By: Relevance
“…While the machined surface implants were the most common (n=13), surface modifications were also employed (sandblasted and acid-etched surfaces [ 11 12 13 ], acid-etched surfaces [ 14 ], and hydroxyapatite-coated surfaces [ 15 ]). The implant surface properties were not reported in 6 studies [ 16 17 18 19 20 21 ].…”
Section: Resultsmentioning
confidence: 99%
“…While the machined surface implants were the most common (n=13), surface modifications were also employed (sandblasted and acid-etched surfaces [ 11 12 13 ], acid-etched surfaces [ 14 ], and hydroxyapatite-coated surfaces [ 15 ]). The implant surface properties were not reported in 6 studies [ 16 17 18 19 20 21 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, DM, as a kind of metabolic disorder, has been reported to decrease bone mineral content and retard the process of implant fixation, leading to the implant failure . Previous reports have indicated that an overall reduction in bone turnover rather than excessive bone resorption contributed to DM-induced bone healing impair. , The abnormal osteoblast structure and biological functions at the bone–implant interface play a critical role in the above process . To correct the abnormality, improving metabolic control in DM which reverses impaired bone healing seems to be a good measure but is hardly achieved within a short time for urgent clinical surgery.…”
Section: Discussionmentioning
confidence: 99%
“…9,36 The abnormal osteoblast structure and biological functions at the bone−implant interface play a critical role in the above process. 37 To correct the abnormality, improving metabolic control in DM which reverses impaired bone healing seems to be a good measure 38 but is hardly achieved within a short time for urgent clinical surgery. Therefore, it is an urgent need to search for alternative valuable improvement strategies to promote rapid implant osseointegration in diabetics.…”
Section: Discussionmentioning
confidence: 99%
“…This work was to understand the effect of n-HA/PA66 material prepared in this experiment on bone defect healing of diabetic implants. Alloxan can selectively destroy pancreatic β cells, cause cell failure, block cell secretion of insulin, and then cause diabetes [ 27 ]. The results showed that the weight of experimental rabbits was considerably inferior to that of normal rabbits, while the blood glucose level was always higher than that of normal rabbits.…”
Section: Discussionmentioning
confidence: 99%